2008
DOI: 10.1080/10641950701825887
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Parameters During Normal and Hypertensive Pregnancy in Rats: Evaluation of Renal Salt and Water Transporters

Abstract: Our results suggest that tubule transporter variants may mediate the hemodynamic adaptations seen during pregnancy, although we cannot rule out the hypothesis that other factors are also mediating hemodynamic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…The observed down-regulation of AQP2 mRNA and protein expression during pregnancy is in direct contrast to evidence published previously demonstrating a pregnancy-related up-regulation of AQP2 in renal papillae [44,45]. Segmental differences in aquaporin protein expression in the kidney have been reported by other groups.…”
Section: Discussioncontrasting
confidence: 91%
“…The observed down-regulation of AQP2 mRNA and protein expression during pregnancy is in direct contrast to evidence published previously demonstrating a pregnancy-related up-regulation of AQP2 in renal papillae [44,45]. Segmental differences in aquaporin protein expression in the kidney have been reported by other groups.…”
Section: Discussioncontrasting
confidence: 91%
“…4) and also indicate that the larger transport capacity in the distal nephron of the female kidney renders women better equipped to handle (i.e., retain a significantly more of) the larger filtered load in pregnancy. Nevertheless, to completely compensate for the heightened load in pregnancy, further alternations in tubular transport are required [32,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these simulations indicate that tubular hypertrophy, activation of reserve NHE3 capacity, and the higher (baseline) distal transport capacity together can attenuate the excessive natriuresis, diuresis, and kaliuresis that is predicted to arise due to hemodynamics changes similar to those observed in pregnancy. However, to achieve baseline urine output and excretion, additional changes are required, including transport adaptation along the distal segments [32].…”
Section: Sex Differences In Segmental Transport Under Baseline Conditmentioning
confidence: 99%
“…Normal pregnancy is characterized by increased blood volume, which is a fundamental requirement for adequate blood supply to the fetus. The expansion of the extracellular volume is primarily determined by renal sodium and water retention mediated by the upregulation of the water channel AQP2 [ 52 ] and the main sodium tubular transporters [ 7 ]. Indeed, in the present study we observed an upregulation of the NHE 3 and AQP2 mRNAs, suggesting they play a role in the sodium and water reabsorption in the control P group.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy also imposes a necessary expansion of the extracellular volume (ECV) by sodium and water retention via mechanisms involving changes in the expression of tubular transporters. We recently demonstrated that the expression of renal transporters including the Na-Cl and Na-K-2Cl cotransporters, Na-H exchanger, and aquaporin 2 is increased during pregnancy in rats [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%